TANGGUNG JAWAB PELAKU USAHA TERHADAP KONSUMEN APARTEMEN LA CITY YANG TIDAK MEMPEROLEH UNIT APARTEMEN BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Achmad Fazrin; Siti Nurbaiti (Fakultas Hukum Universitas Tarumanagara, 2020)
Consumer disputes often occur besides consumers who do not understand their rights, also because of the position of consumers who do not meet the conditions where consumers are in a weak position. Apartments that accept customers do not accept apartment units that they buy, even though consumers receive approval as customers in good faith, the apartment units as agreed, then it belongs to PT Spekta Properti Indonesia apartments to the units. The formulation of the problem in this renewal is regarding business liability which is not submitted by the apartment unit to the customer based on law number 8 of 1999 concerning consumer protection. This writing uses legal research methods for academic purposes by requesting approval, the type of legal material used is primary legal material and is supported by secondary legal material namely interview data. The results of research on businesses undertaken are not responsible because consumers do not obtain apartment units that they buy, then based on Article 19 (1) UUPK which requires businesses to be responsible for consumer losses, compensation suffered by consumers based on Article 19 (2) UUPK. As a form of business accountability must submit apartment units purchased by consumers and comply with Article 19 (1) UUPK.